The Impact of Technological Backwardness on the Sustainability of MSMEs in Ciasihan Village - Arham; Abdul Qodir (Trescode Green Organization, 2025)
The rapid advancement of digital technology has brought transformative changes to the global economy, impacting the competitiveness and sustainability of businesses across various sectors. However, not all regions have benefited equally from this transformation. This study aims to analyze the impact of technological underdevelopment on the sustainability of micro, small, and medium enterprises (MSMEs) in Ciasihan Village, a rural area in Indonesia that still faces digital inequality. The study used a qualitative descriptive approach through in-depth interviews and direct observation with ten MSME owners operating in various sectors, including food processing, services, and handicrafts. The findings indicate that MSMEs in Ciasihan Village face persistent barriers such as limited digital literacy, unstable internet connectivity, and a lack of institutional support. These obstacles hinder their ability to participate in the digital marketplace and effectively adopt technological innovations. However, MSMEs that have adopted even simple digital tools, such as social media marketing and mobile-based payment systems, have shown significant improvements in market reach and operational efficiency. The study concludes that digital readiness and ongoing literacy training are key determinants of achieving sustainable business growth among rural MSMEs. Strengthening the digital ecosystem in rural areas through government collaboration, educational support, and infrastructure development is crucial to minimizing the technology gap and ensuring inclusive economic progress.